Pete the cat and the bedtime blues - Dean, James 1969-; Dean, James, 1957- (New York, NY : Harper, an imprint of HarperCollins Publishers, 2023)
"Pete the Cat wants to go to sleep, but his animal friends want to stay up and play"--Provided by publisher.
School Library Journal
School Library Journal, June 2015
K-3
K-3
English
Keywords: Animals -- Juvenile fiction; Bedtime -- Juvenile fiction; Cats -- Juvenile fiction; Sleepovers -- Juvenile fiction; Animals -- Fiction; Bedtime -- Fiction; Cats -- Fiction; Sleepovers -- Fiction; Animals -- Fiction; Bedtime -- Fiction; Cats -- Fiction; Sleeping customs -- Fiction; Picture books; Stories in rhyme